Innovation Management by Promoting the Informal Artistic, Experience-based, Playful - Böhle, Fritz; Bürgermeister, Markus; Porschen, Stephanie (Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book explores new approaches to successful innovation - with all uncertainty. Its focal points are management of the informal and a new perspective of human work: innovation work is based on artistic, experience-based and playful action. The book helps recognize and utilize new success potentials for innovation in enterprises. It addresses managers and experts who are interested in promoting innovation in practice. Moreover, scientists will gather new interdisciplinary insights into innovation management and work organization from this book.